Psychological Factors Motivating Male Japanese Workers With Type 2 Diabetes to Engage in Dietary Modifications: A Qualitative Descriptive Study - Kanako Morinishi MS, RN, PHN; Ai Chikada PhD, RN, PHN; Masahito Ogura PhD, MD; Nobuya Inagaki PhD, MD; Kazuko Nin PhD, RN (SAGE Publishing, 2023)
Introduction Japanese men with type 2 diabetes mellitus (T2DM) usually encounter work-related difficulties when engaging in dietary modifications. Hence, healthcare providers must understand the psychological factors, such as the needs and goals, that motivate them to engage in dietary modifications. Objective We aimed to describe the psychological factors motivating male Japanese workers with T2DM to engage in dietary modifications. Methods Using a qualitative descriptive design, we conducted semi-structured interviews with 11 male Japanese workers with T2DM and identified categories based on semantic differences using qualitative content analysis. Results The following eight categories emerged: (I want to) demonstrate my skills at work, be able to engage in dietary modifications on my own, avoid unpleasant symptoms caused by eating, avoid burdensome treatment, maintain my healthy life, get positive results in medical examinations, maintain my relationships with others, and enjoy healthy food. Conclusion The factors motivating the participants to engage in dietary modifications were realistic and sincere desires rooted in their ideal lives. Their desire to prioritize work emerged as an important factor. Healthcare providers should identify an individual's ideal daily life, including work aspects, and encourage individuals to set realistic and valuable goals.